Mechanisms Associated with Protective Effects of Ginkgo Biloba Leaf Extracton in Rat Cerebral Ischemia Reperfusion Injury. Issue 19 (2nd October 2019) - Song, Wei; Zhao, Jun; Yan, Xu-Sheng; Fang, Xin; Huo, Dong-Sheng; Wang, He; Jia, Jian-Xin; Yang, Zhan-Jun
ABSTRACT: Cerebral infarction occurs as a consequence of cerebral ischemia-reperfusion injury (CIRI). Ginkgo biloba leaf extract (GbE) is composed predominantly of active ingredients such as flavonoids and terpene lactones and often used to treat cerebrovascular diseases. However, the mechanisms underlying the use of this herbal extract to treat cerebrovascular-mediated damage are not known. The aim of this study was to examine the effectiveness of administration GbE to ameliorate the observed consequences of CIRI. The following parameters were measured: (1) behavioral score (2) infarct area (3) the content of serum malondialdehyde (MDA) as well as activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and (4) interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNF-α) expression levels in the infarcted brain tissue. Data demonstrated that treatment with GbE to CIRI rats resulted in significant reduction in cerebral-infarcted area associated with improvement in behavioral score. GbE was found to decrease serum MDA levels concomitant with elevated activity levels of SOD and GSH-PX. Immunohistochemistry and Western blot analysis showed that GbE significantly lowered the levels of IL-6 and TNF-α in the infarcted brain tissue. Data suggest that GbE may be therapeutically effective in improving behavioral score in CIRI rats through reduction of oxidative stress and anti-inflammation in the cerebral infarction region.